Peningkatan Kemampuan Degradasi ZnO Terhadap Rhodamin B Dengan Impregnasinya Pada Karbon Aktif Dari Ampas Tebu - Winda Anisa; Miftahul Khair (Departemen Kimia FMIPA UNP, 2022)
Research has been carried out with the aim of knowing the characteristics of activated carbon made from bagasse waste to be used as a support for zinc oxide (ZnO) catalysts using the impregnation method and the ability of the catalyst to degrade Rhodamin B dyes. Activated carbon is impregnated with Zn(NO3)2.6H2O with variations activated carbon 5%, 10%, 15%, 20%, and 25% to 15 gram mass of Zn(NO3)2.6H2O. The impregnated KA/ZnO was then contacted with 10 ppm Rhodamine B dye with a degradation time of 120 minutes. The mass of KA/ZnO used was 25 mg, 50 mg and 75 mg. The FTIR (Fourier Transform Infra Red) results of the KA/ZnO catalyst show that Zn-O molecules have entered into the pores of the activated carbon marked by the appearance of absorption peaks at wavelengths of 426.28 cm-1, 419.52 cm-1, and 437.85 cm-1 . The results of UV-Vis spectrophotometer measurements obtained the highest degradation percentage of Rhodamin B dye, namely 88.23% at 10% KA/ZnO with a catalyst mass of 75 mg.